Realization of Novel Biomedical and Electromagnetic Devices Using Additive Manufacturing and Laser Micromachining - Sadeqi, Aydin. (Tufts University. Tisch Library., 2021)
Thesis (Ph.D.)--Tufts University, 2021.; Submitted to the Dept. of Electrical Engineering.; Advisor: Sameer Sonkusale.; Committee: Bingnan Wang, Tom Vandervelde, Shuchin Aeron, and Qiaobing Xu.; Keyword: Engineering.